Over provisioning-centric QoS-routing mechanism for the communication paradigm of future internet 4WARD proposal - Neto, Augusto (2012)
The FP7 4WARD clean-slate Project envisions overcoming the limitations of current Internet by redefining it to efficiently support complex value-added sessions and services, such as location-based, health-care, critical-mission, and geo processing. The list of networking innovations from 4WARD’s Future Internet (FI) proposal includes a new connectivity paradigm called Generic Path (GP), a common representation for all communications. From the networking point of view, a GP is mapped to a communication path for data propagation. For that, GP architecture relies on routing mechanism for selecting best communication paths. In order to assure reliable communications, the routing mechanism must efficiently provision QoS-aware multi-party capable paths, with robustness functions, while keeping network performance. Therefore, this paper proposes the QoS-Routing and Resource Control (QoS-RRC) mechanism to deal with the hereinabove requirements by means of an over provisioning-centric (bandwidth and paths) approach. QoS-RRC achieves scalability by avoiding per-flow operations (e.g., signaling, state storage, etc.). Initial QoS-RRC performance evaluation was carried out in Network Simulator v.2 (NS-2), enabling drastic reduction of overall signaling exchanges compared to per-flow solutions.